Low dose ATG-Fresenius for GVHD prophylaxis: a comparative study with ATG-Thymoglobulin - Falicovich, Itai; Nachmias, Boaz; Elias, Shlomo; Zimran, Eran; Shaulov, Adir; Stepensky, Polina; Avni, Batia; Grisariu, Sigal (Frontiers in Immunology, 2025)
BackgroundAnti-Thymocyte Globulin (ATG) is commonly used to prevent graft-versus-host disease (GVHD), but the optimal dosage and type of ATG remains to be determined.ObjectiveWe compared retrospectively the safety and efficacy outcomes of allogeneic transplantation using low-dose ATG-Fresenius (15mg/kg) and ATG-Thymoglobulin (10mg/kg) for GVHD prevention.Study designNinety-eight patients were included, with 46 in the ATG-T group and 52 in the ATG-F group. The median age was 48 years in the ATG-T group (range 20-71) and 50 years in the ATG-F group (range 18-73). Baseline characteristics were similar, with slightly more HLA mismatched donors and single-agent cyclosporine GVHD prophylaxis use in the ATG-T group. Additionally, the ATG-F group had more myeloid leukemia and myelodysplastic syndrome patients, while the ATG-T group had more lymphoma patients.ResultsThe cumulative incidence of acute GVHD (aGVHD) grade II-IV and chronic GVHD (cGVHD) showed no significant differences. Multivariate analysis indicated that donor HLA mismatch influenced aGVHD risk significantly (p=0.005), and myeloablative conditioning increased cGVHD risk. Bacteremia and CMV reactivation rates were similar, but EBV DNA viremia was higher in the ATG-T group (22% vs. 8%, p=0.047), with one case of Post-Transplant Lymphoproliferative Disorder (PTLD) in the ATG-T group. Cumulative incidence of overall survival (OS), relapse incidence, non-relapse mortality (NRM) and GVHD free, Relapse free Survival (GRFS) did not significantly differ.ConclusionsThis study highlights the safety and efficacy of low-dose ATG-F compared to a relatively high dose ATG-T. Prospective studies are necessary to validate the safety and efficacy of low dose ATG-F for GVHD prevention.